Fish Biodiversity in Bunter Lake Pangkalan Baru Village, Siak Hulu District, Kampar Regency Riau Province - Mhd Rizqo Pratama; Deni Efizon; Efawani Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
AbstractThe Bunter Lake is an oxbow lake that receive water from the Kampar River during the rainy season. As the water flew to the lake, many types of fishes may be entered the lake. On the other hand, when there is no water input from the river, the fishes were trapped in the lake and fish catching activities conducted may affects the population of the fish in general. The presence of fish coming from the river and the fishing activities in the lake may affects the biodiversity of the fish in general. To understand the biodiversity of the fish in the lake during the rainy season, a study has been conducted on July to August 2021. Samplings were conducted 6 times, 3 times during the rain/ flood and 3 times when there was no rain. The fish was captured using gillnet, 0.5 and 3 inch mesh size. The fish captured were identified. Results shown that there were 18 fish species that were belonged to 6 families. There were family Cyprinidae (Thynnichthys polylepis, T. thynnoides, Barbodes schwanenfeldi, Rasbora argyrotaeina, Barbichthys laevis, Osteochilus hasselti, Puntius bulu, Oxygaster anomarula, O. melanopleurus, Hampala macrolepidota dan Amblyrhynchichthys truncates), family Bagridae (Mystus nigriceps, M. nemurus), family Siluridae (Ompok hypophthalmus, Phalacronotus apogon), family Eleotridae (Oxyeleotris marmorata family Notopteridae (Notopteridae boornensis) The diversity index value (H') was 2.12, the dominance index (C) was 0.36 and the uniformity index (E) was 0.70. These data indicate that the diversity of fish in the Bunter Lake was moderate. As the dominance index value (C) as well the uniformity index value (E) were relatively low , the environmental condition of the lake is balance. Keywords: oxbow lake, rainy season, fish capture, diversity index